Catalisadores superácidos a base de TiO2 para hidrólise da celulose - Albuquerque, Nilson José Araújo de (2015)
In our times, the chemical catalysis of the hydrolysis reaction, solubilization and degradation of cellulose, the base metal has attracted great interest due to the large potential in terms of activity and selectivity, or the possibility of developing products and / or chemical processes that are associated with the use of clean technologies. In this work the catalytic systems MoO3 / TiO2 and SO4 -2 / TiO2 were synthesized by sol-gel method, followed by wet impregnation of molybdenum or sulfate in the application for conversion of cellulose into sugars, a process called hydrolysis. After synthesis, the same were characterized by checking the crystal structure, the presence of phases, morphology and dispersion of material on the support and through the techniques of infrared spectroscopy. However, after the impregnation of molybdenum or sulfate in the textural changes occurred. Thermogravimetric curves were used in determining the composition of molybdenum and sulfate present in the materials. Through the analysis of infrared absorption of pyridine, was observed sites acids in the material, which provided catalytic activity toward the hydrolysis reactions, solubilization and degradation of cellulose.